Psychological interference, liberty and technology. (May 2022) - Sætra, Henrik Skaug; Mills, Stuart
Abstract: Power and the use of force are central concerns in liberal political theory. Yet, it is claimed that liberal theory fails to account for the power that is exerted through, for example, personalised nudging based on Big Data. We dispute this claim and through a reappraisal of the concept of negative liberty we show how psychological interference can be both coercive and manipulative. This reappraisal is partly achieved through an examination of psychological equivalents of physical interference, in order to highlight the arbitrariness of excluding the non-physical from consideration. The liberal understanding of liberty and interference here provided enables us to see how power is exerted through technology. It thus provides a novel contribution to the analysis of the liberty reducing effects of new technologies combined with a lack of privacy and a will to manipulate, based on an individualist liberal theory argued to be incapable of just that. Highlights: Power, interference, and force are key concepts in liberal theory. Technology allows for the use of what we label psychological interference. Such interference is often opaque, and overlooked by traditional theories. We show that such interference is both manipulative and coercive. We also show that liberal theory is equipped to deal with these phenomena.